DETERMINAN ISLAMIC HUMAN DEVELOPMENT INDEX (IHDI) PROVINSI JAWA TIMUR TAHUN 2001-2016 - Reni Mustika Putri; Karjadi Mintaroem (Universitas Airlangga, 2019)
This study aimed to determine the effect of economic growth, government expenditure, and ZIS distribution on IHDI in East Java in 2001-2016. The research method using quantitative approach by usingOrdinary Least Square (OLS) to see the elasticity of independent variables to dependent variables. The result of statistical test analysis showed that three of four independent variables had a positive and significant value on IHDI, which were: economic growth, goverment expenditure on education, and government expenditure on health. Zakat, infaq, sadaqah variables have nosignificant effect on IHDI.Keywords: Economic Growth, Education Expenditure, Health Expenditure, ZIS Distribution, Islamic Human Development IndexREFFERENCESAnto, M. Hendrie. 2009. Introducing an Islamic Human Development Index(IHDI) to Measure Development in OIC Countries. Islamic EconomicStudies, Vol. 19 No.2.Baeti, Nur. 2013. Pengaruh Pengangguran, Pertumbuhan Ekonomi, danPengeluaran Pemerintah Terhadap Pembangunan Manusia Kabupaten/Kota Di Provinsi Jawa Tengah Tahun 2007-2011. ISSN 2252-6889.Beik,Irfan Syauqi & Arsyianti, Laily Dwi. 2015. Ekonomi Pembangunan Syariah. Bogor : Penerbit IPB Press.Effendi, Agus dan Bahruddin Fananny. 2008. Zakat : Kajian Berbagai Mazhab.Bandung. PT Remaja Rosdakarya.Fiqhyany. 2014. Dampak Shadaqah Pada Keberlangsungan Usaha. Surabaya.Skripsi tidak diterbitkan. Universitas Airlangga Surabaya.Jhingan, M.L. 2010. Ekonomi Pembangunan dan Perencanaan. Jakarta. PT. Raja Grafindo Persada.Mankiw, N. Gregory dkk. 2012. Pengantar Ekonomi Makro Edisi Asia Volume 2. Terjemahan oleh Biro Bahasa Alkemis. Jakarta : Salemba Empat.Mirza, Denni Sulistio. 2012. Pengaruh kemiskinan, Pertumbuhan Ekonomi, danBelanja Modal Terhadap Indeks Pembangunan Manusia di Jawa Tengah Tahun 2006-2009. Economics Development Analysis Journal. ISSN 2252-6560.Murniarti, Rina & Irfan Syauqi Beik. 2011. Pengaruh Zakat Terhadap Indeks Pembangunan Manusia dan Tingkat Kemiskinan Mustahik : Studi Kasus Pendayagunaan BAZNAS Kota Bogor. ISSN 2337-6333.Naf’an. 2014. Ekonomi Makro: Tinjauan Ekonomi Syariah.Cetakan kesatu. Yogyakarta: Graha Ilmu. Nurzaman MS. 2010. Zakat and human development: an empirical analysis on poverty alleviation in Jakarta, indonesia. Center for Islamic economics and finance, Qatar faculty of Islamic studies, Qatar foundation. p 1-26.Ranis, Gustav. 2004. Human Development and Economic Growth. Working Papers 887. Economic Growth Center. New Harven : Yale University.Sholihin, Ahmad Ifham. 2010. Buku Pintar Ekonomi Syariah. Jakarta. PT Gramedia Pustaka Utama.Soyomukti, Nurani. 2008. PendidikanBerperspektif Globalisasi.Yogyakarta. Ar–Ruzz Media.